Deep learning in biotechnology: Comparing PjBL and direct instruction on students’ critical and creative thinking skills - Isrul, Muhammad; Azis, Andi Asmawati; Nurhayati, B.; Daud, Firdaus; Palennari, Muhiddin (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2026)
Developments in 21st-century education highlight critical and creative thinking as essential competencies that must be strengthened in biology learning, especially in biotechnology, which requires analysis, problem-solving, and science-based decision-making. However, empirical evidence on the integration of deep learning approaches into project-based learning (PjBL) and direct instruction models in biotechnology learning remains limited. This study aimed to analyze the effect of integrating deep learning approaches into PjBL and direct instruction on students’ critical and creative thinking skills. A quasi-experimental non-randomized pretest–posttest control group design was employed. The participants were 72 twelfth-grade students from State High School 3 Makassar, equally assigned to two groups. The experimental group learned through PjBL integrated with deep learning, whereas the control group learned through direct instruction integrated with deep learning. Data were collected using critical and creative thinking skills tests and analyzed using ANCOVA. The results showed that the instructional model significantly affected students’ critical thinking skills, with p-value = 0.005 (p < 0.05), and creative thinking skills, with p-value = 0.018 (p < 0.05). Students taught through PjBL integrated with deep learning obtained higher scores than those taught through direct instruction. Therefore, this model is more effective for biotechnology learning overall.